Disrupted interhemispheric functional connectivity in chronic insomnia disorder: a resting-state fMRI study - Zhou F (Dove Medical Press, 2018)
Fuqing Zhou,1,2 Yanlin Zhao,1,2 Muhua Huang,1,2 Xianjun Zeng,1,2 Bo Wang,1,2 Honghan Gong1,2 1Department of Radiology, The First Affiliated Hospital, Nanchang University, Nanchang, China; 2Neuroradiology Lab, Jiangxi Province Medical Imaging Research Institute, Nanchang, China Background: Abnormalities in both cerebral structure and intrinsic activity have been increasingly reported in patients with chronic insomnia disorder (CID). However, the interhemispheric integration function in CID is still not well understood. Functional homotopy reflects an essential aspect of the intrinsic functional architecture involved in interhemispheric coordination. Methods: In this study, voxel-mirrored homotopic connectivity (VMHC) was used to analyze the patterns of interhemispheric intrinsic functional connectivity in patients with CID (n=29). Results: Reduced homotopic connectivity was observed in the middle occipital/posterior middle temporal gyrus in CID patients relative to control subjects. Further analyses demonstrated different insomnia-related heterotopic connectivity patterns in the right and left middle occipital/posterior middle temporal gyrus. Furthermore, within the CID group, the connectivity coefficient within the connectivity network of the middle occipital/posterior middle temporal gyrus was associated with anxiety measures. Conclusion: Negative significant findings of group differences were found in terms of both the local gray matter density and fractional anisotropy of the white matter skeletal measures in this study; this structural finding, together with the results of VMHC, suggested that disruptions in the intrinsic functional architecture of interhemispheric communication associated with CID can be observed in the absence of detectable microstructural or local morphometric changes in white and gray matter. Keywords: homotopic connectivity, interhemispheric integration, voxel-mirrored homotopic connectivity, chronic primary insomnia, sleep disorders, resting-state fMRI